Data Generation in Science and Technology - Gopinath, M. A. (Journal of Information and Knowledge, 1981)
Discusses the process of generation of data in science and technology. Identifies (1) the cause for data generation; (2) the types of data generated; (3) the procedures of data generation. Discusses in detail the procedures for generation of experimental data. Identies the role of critical variable in data generation and correlation. The data generation is projected as an endless cycle.